1983
DOI: 10.4294/jpe1952.31.349
|View full text |Cite
|
Sign up to set email alerts
|

Rheological structure of the earth's mantle derived from glacial rebound in Laurentide.

Abstract: The theological structure of the earth's mantle was determined based on data from the postglacial isostatic adjustment in Laurentide. According to a linear analysis with a Newtonian rheology, the apparent viscosity derived from the observed relative sea level data is about ten times larger in the central part of the glaciated region than that in the surrounding region. Namely, the and estimated remaining uplift, does not reflect the non-linearity of the means that the lower mantle viscosity is greater than 102… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
(59 reference statements)
2
15
0
Order By: Relevance
“…One of the first interpretations is due to Nakada (1983) Focussing on RSL data from region RG and based on forward calculations, Mitrovica (1996) showed that the RG relaxation time requires Table VI. Table VI f-3.0.tex; 14/06/2005; 9:50; p.32…”
Section: Previous Estimatesmentioning
confidence: 99%
“…One of the first interpretations is due to Nakada (1983) Focussing on RSL data from region RG and based on forward calculations, Mitrovica (1996) showed that the RG relaxation time requires Table VI. Table VI f-3.0.tex; 14/06/2005; 9:50; p.32…”
Section: Previous Estimatesmentioning
confidence: 99%
“…In the analysis with Newtonian rheology, the apparent viscosity derived from the observed RSL in Churchill is about ten times larger than that in Southampton Island (NAKADA, 1983). This tendency seems to be detected in the study by Wu and PELTIER (1982).…”
mentioning
confidence: 56%
“…Recently PELTIER (1984) showed that the RSLs at the forebulge region strongly depend on the thickness of the elastic lithosphere, and that the misfit at the forebulge region in Laurentide can be improved by the rheological model with the elastic lithosphere of about 200 km. NAKADA (1983) showed that the RSLs in Laurentide do not depend on the elastic lithosphere with thickness of less than 100 km. As the thickness of the elastic lithosphere is greater, the deformation with larger wavelength is affected by the elastic lithosphere.…”
mentioning
confidence: 99%
“…Sea-level variations in North America have extensively been examined to estimate the rheological structure of the Earth's mantle (e.g., Cathles, 1975;Wu and Peltier, 1983;Nakada, 1983). But the changes at sites along the east coast of North America such as Boston and New York, close to the margins of Laurentide ice sheets, are equally sensitive to the rheology of the mantle as to the detailed description of the load; generally the latter is inadequately known for the purpose of estimating the Earth's viscosity Lambeck, 1987, 1988b).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Peltier and Andrews (1976), Wu and Peltier (1983) and Tushingham and Peltier (1992) have argued that the sea-level predictions based on a uniform viscosity model can explain the global data base of relative sea-level changes. There are, however, a number of studies supporting a major increase in viscosity from the upper to lower mantle (e.g., Walcott, 1980;Nakada, 1983;Nakada and Lambeck, 1989;Nakada and Lambeck, 1991;Forte and Mitrovica, 1996). From independent arguments using the geoid anomalies around the subduction zone, Hager (1984) has also suggested a substantial increase in viscosity across the 670 km seismic discontinuity.…”
Section: Introductionmentioning
confidence: 99%